The customer complaining behavior : why customers do not complain - Järvenpää, Jarno (2017)
The field of the marketing has been under change since services gained attention under 1970s. The customer behavior and the relationship marketing gained it focus in the 1990s. At the same time, the need for understanding the customer complaining be-havior was noticed being vital for service management. This research is a response for the Tronvoll’s (2012) call for better understanding the customer complaining behavior. Especially, he called for investigation of what makes the customers act and behave in certain way. The intention of this study was to explore triggers, inhibits and motivators, which affect to the complaining behavior and explore the customer complaining behavior. The theoretical framework builds on the theories of the customer complaining be-havior, the service quality and the service experience. The customer complaining behav-ior was based on the Hirschman’s (1975), the Singh’s (1988) and the Tronvoll’s (2012). The Tronvoll’s model was selected for the theoretical framework. The method of the analysis was to search for holistic features and patterns, which was supported by the discourse analysis, the content analysis and the theme analysis. The research data con-sisted of the two parts: 1) narratives of the bad service experiences and 2) thematic inter-views. The results showed that there are four types of moderators of the complaining be-havior: the psychological, the experimental, the presumption and the personal types of the customer complaining behavior. These types have a different input on the dimen-sions of the Tronvoll’s model. The types have a different kind of role on influencing cus-tomers do stand from complain; act towards third parties and to complain directly to the service provider. These findings highly support the earlier findings of the customer complaining behavior and clarify the influencer types behind the complaining behavior